(untitled) (Bulletin of criminological association of Ukraine, 2024)
The article is devoted to a criminological analysis of the state of human trafficking in the world and in Europe, in particular. On a global scale, organized criminal groups exploit the most vulnerable sections of the population for profit, with complete disregard for human safety and dignity. Human trafficking and migrant smuggling are low-risk, high-profit criminal activities that increasingly use sophisticated and technological methods to expand their reach. Human trafficking has a transnational character, its victims are representatives of both sexes and of different ages. A special form of human trafficking is illegal transactions involving people for the purpose of extracting organs and anatomical materials. It has been established that over the last decade, a significant increase in human trafficking has been recorded in the EU. The situation was significantly worsened by the start of Russia’s full-scale aggressive war against Ukraine and the flow of millions of refugees from Ukraine.